Haematologists’ experiences implementing patient reported outcome measures (PROMs) in an outpatient clinic: a qualitative study for applied practice - Stine Thestrup Hansen; Mette Kjerholt; Sarah Friis Christensen; Bibi Hølge-Hazelton; John Brodersen (Journal of Patient-Reported Outcomes, 2019)
Abstract Background The patient-doctor relationship is crucial to provide person-centred care, allowing the alleviation of symptom burden caused by disease or treatment. Implementing Patient Reported Outcome Measures (PROMs) is suggested to inform the decision-making process and lead to initiation of care. Yet there are knowledge gaps regarding how meaningful it is to incorporate PROMs in clinical settings. The aim of this study was to investigate haematologists’ experiences when PROMs were implemented in an outpatient setting. Methods Fourteen participant observations, 13 individual interviews and three in-depth interviews were conducted with haematologists, guided by the qualitative methodology Interpretive Description. Analysis was inspired by Habermas’ critical theoretical framework. Results The haematologists included were characterised by dichotomous experiences with PROMs, either resistant to or supporting their implementation. None were observed to elaborate on PROMs during consultations: instead, primary attention was spent discussing the hematological agenda dictated by the system. Conclusion The use of PROMs for individualized care was linked with extensive uncertainties and PROMs were not requested by the haematologists. To improve individualized care, other approaches may be more suitable. If PROMs are to be incorporated into future clinical practice, they should be tested tothe specific patient group and involve relevant users.